Le semis direct : Un système en extension à la coopérative agricole Khemisset Chaouia - Benaouda H.; El Gharras O.; Vadon B.; Farouq E. (Troisièmes rencontres méditerranéennes du semis direct, 2006)
Most farms within the Khemisset Chaouia Cooperative have deep clay soils. In this semiarid area, plowing after summer, when the soil is very dry, is a difficult operation. For plowing, farmers have to wait for the first significant rainfall. This situation contributes to reducing the length of the growing period, which is already reduced because of recent climatic changes. The no-tillage system offers the possibility of early planting in the season without waiting for the first significant rainfall. No-tillage can be one of the best solutions to reduce the drought effects in semiarid zones.Following the excellent results obtained in on-farm trials, farmers have become aware of the importance of adopting the no-tillage system in their cooperative. In the 2003-2004 cropping season 7 hectares were cultivated under this system. In the 2005-2006 cropping season, the cooperative is planning to plant 160 hectares of cereals and legumes using the no-tillage system.
3. Mediterranean Meeting on no Tillage, 2006/03/23-25, Zaragoza (Spain)